2015
DOI: 10.1016/s2213-2600(15)00095-8
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF assay for the diagnosis of pulmonary tuberculosis in children: a systematic review and meta-analysis

Abstract: Summary Background Microbiological confirmation of childhood tuberculosis is rare because of the difficulty of collection of specimens, low sensitivity of smear microscopy, and poor access to culture. We aimed to establish summary estimates for sensitivity and specificity of of the Xpert MTB/RIF assay compared with microscopy in the diagnosis of pulmonary tuberculosis in children. Methods We searched for studies published up to Jan 6, 2015, that used Xpert in any setting in children with and without HIV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
244
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 284 publications
(266 citation statements)
references
References 34 publications
15
244
2
5
Order By: Relevance
“…In its 2013 policy update, the WHO reported a pooled sensitivity of 66% for Xpert compared to culture with a pooled specificity of 98% (30). A second comprehensive metaanalysis through December of 2014 reported a pooled sensitivity of 62% (95% confidence interval [CI], 44% to 80%) for Xpert compared to culture of sputum specimens and a pooled specificity of 99% (95% CI, 97% to 99%) ( Table 3) (33). The same analysis reported that the odds of a positive Xpert result were four times greater in smear-positive pediatric samples than in smear-negative samples.…”
Section: Molecular Detection Methodsmentioning
confidence: 99%
“…In its 2013 policy update, the WHO reported a pooled sensitivity of 66% for Xpert compared to culture with a pooled specificity of 98% (30). A second comprehensive metaanalysis through December of 2014 reported a pooled sensitivity of 62% (95% confidence interval [CI], 44% to 80%) for Xpert compared to culture of sputum specimens and a pooled specificity of 99% (95% CI, 97% to 99%) ( Table 3) (33). The same analysis reported that the odds of a positive Xpert result were four times greater in smear-positive pediatric samples than in smear-negative samples.…”
Section: Molecular Detection Methodsmentioning
confidence: 99%
“…Although culture is currently considered the best available reference standard, its sensitivity for detecting CPTB is acknowledged to be imperfect (3,4,10). The culture reference standard thus inevitably leads to true CPTB case patients being misclassified as being negative for CPTB.…”
mentioning
confidence: 99%
“…5 In a recent systematic review, Detjen et al reported sub-optimal sensitivity (51-81%) of Xpert in expectorated/induced sputum and gastric lavage samples in children, calling for further research to improve pediatric TB diagnostics. 35 However, none of the studies in this review were conducted in children. There are ongoing studies evaluating urine samples in TB patients including children; however, data from these studies are not yet available.…”
Section: Discussionmentioning
confidence: 99%